2018
DOI: 10.1109/mvt.2018.2811644
|View full text |Cite
|
Sign up to set email alerts
|

Full-Duplex Communications: Performance in Ultradense mm-Wave Small-Cell Wireless Networks

Abstract: Theoretically, full-duplex (FD) communications can double the spectral-efficiency (SE) of a wireless link if the problem of self-interference (SI) is completely eliminated. Recent developments towards SI cancellation techniques have allowed to realize the FD communications on low-power transceivers, such as small-cell (SC) base stations. Consequently, the FD technology is being considered as a key enabler of 5G and beyond networks. In the context of 5G, FD communications have been initially investigated in a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 15 publications
(36 reference statements)
0
43
0
Order By: Relevance
“…At iteration κ + 1 of the proposed algorithm, the successive convex program follows as the proposed ICA-CR-PF algorithm to solve (12). Without loss of optimality, the constant penalty parameters can be uniformly selected through ̺ max{̺ d kj , ̺ u ℓm } k,j∈K, ℓ,m∈L , as proved in Appendix C. With an appropriate choice of ̺, the ICA-CR-PF algorithm provides an optimal solution to the original problem (11). Further discussions on the choice of the penalty parameter ̺ are given in Section VI-C.…”
mentioning
confidence: 99%
“…At iteration κ + 1 of the proposed algorithm, the successive convex program follows as the proposed ICA-CR-PF algorithm to solve (12). Without loss of optimality, the constant penalty parameters can be uniformly selected through ̺ max{̺ d kj , ̺ u ℓm } k,j∈K, ℓ,m∈L , as proved in Appendix C. With an appropriate choice of ̺, the ICA-CR-PF algorithm provides an optimal solution to the original problem (11). Further discussions on the choice of the penalty parameter ̺ are given in Section VI-C.…”
mentioning
confidence: 99%
“…The work in [24] studied zero forcing and beam steering methods to mitigate the self-interference channel and highlighted the importance of more efficient methods to deal with the analog beamforming constraint on constant modulus. The authors in [25] aimed to minimize the total data queue buffer length in ultra-dense networks, and they have shown that the full-duplex outperformed half-duplex transmissions with an increasing density of small cell base stations. The work in [26] proposed hybrid beamforming for bidirectional full-duplex, and aimed to minimize the self-interference power.…”
Section: Related Workmentioning
confidence: 99%
“…We can solve the problem (25) in closed form using complex derivatives [35], whose optimal solution f BB ⋆ BS is…”
Section: Baseband Precoders Blockmentioning
confidence: 99%
“…With the deployment of fifth generation (5G) networks likely to occur in the near future, the role of unmanned aerial vehicles (UAVs) in 5G networks is expected be prominent. Already, diverse applications involving multi-UAV use cases have been envisaged, such as UAV-based cellular communications in disaster areas [1] and geographical surveying [2].…”
Section: Introductionmentioning
confidence: 99%